Self-Confidence of Venezuelan Migrant Entrepreneurs in Colombia (2022)
This study determines the personality and behavioural factors related to pull motivation that explains the self-confidence of Venezuelan migrant entrepreneurs. Using a quantitative approach, this study conducted a survey with 88 migrants who own productive units in the urban area of Gramalote, North of Santander, in Colombia. This study examines the association between the variable ‘perception of having self-confidence’ with demographic and motivational contextual factors. Fisher’s exact test was used to determine the evidence of a statistically significant association between the variables. The findings of the multivariate multinomial logistic regression model suggest that the factors related to a high level of self-confidence are gender, perception of ability to take advantage of opportunities, perception of demanding efficiency and quality and perception of taking risks. These factors are to be considered in the policies of the Colombian state regarding education programmes and the formalisation of the labour market with a gender approach in a post-pandemic context. Given that the COVID-19 pandemic caused a crisis in countless aspects, one of which was in the labour market, this study is relevant because it analyses self-confidence as a driver of entrepreneurial development.